2017
DOI: 10.1080/09546634.2017.1329500
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the course and severity of adult acne. Observational cohort study

Abstract: Lifestyle change-related stress, sensitive skin, discontinuation of oral contraceptives and using full-coverage foundations increase severity of AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
3
17
1
2
Order By: Relevance
“…Our study showed that 56.6% patients in the study population presented with late onset acne while 43.33% females suffered from persistent acne which is different from other studies where a majority of patients were in the persistent group. 6,8,9 Acne was mild to moderate in severity in our cohort which was in consonance with the results of Kaminsky et al 9 We noted a significantly different clinical and hormonal difference between the two subgroups (Tables 1 and 2). The mean age of patients with late onset acne was significantly higher than the persistent ones which logically ensues from the late age of presentation (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that 56.6% patients in the study population presented with late onset acne while 43.33% females suffered from persistent acne which is different from other studies where a majority of patients were in the persistent group. 6,8,9 Acne was mild to moderate in severity in our cohort which was in consonance with the results of Kaminsky et al 9 We noted a significantly different clinical and hormonal difference between the two subgroups (Tables 1 and 2). The mean age of patients with late onset acne was significantly higher than the persistent ones which logically ensues from the late age of presentation (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that 56.6% patients in the study population presented with late onset acne while 43.33% females suffered from persistent acne which is different from other studies where a majority of patients were in the persistent group . Acne was mild to moderate in severity in our cohort which was in consonance with the results of Kaminsky et al .…”
Section: Discussionsupporting
confidence: 82%
“…3 A dramatic improvement of the skin appearance on the application site of imiquimod has been observed in patients with XP. [2][3][4][5][6][7] We report two children with XP treated with imiquimod 5% cream, establishing a chemoprophylaxis for cancerization field. Patient 1: A diagnosis of XP was established in a 5-yearold boy with a BCC on his eyelid and multiple hyperpigmented macules on his face (Fig.…”
mentioning
confidence: 99%
“…It has been shown that acne lesions in women aged 30 to 40 occur more frequently in city dwellers, with higher education, performing intellectual work, and not reporting hormonal disturbances (some women report exacerbation of the symptoms in premenstrual period). This type of AV lesions usually occurs for the first time after the period of maturation in women with negative family history of AV, most frequently involves lower part of the face (mandibular and perioral areas, chin) and neck and usually presents as persistent inflammatory lesions (papules, pustules, more rarely nodules, infiltrations and cysts) resolving mostly with post-inflammatory hyperpigmentation [9].…”
Section: Introductionmentioning
confidence: 99%
“…medication or anabolic steroids used in body building and sports) -may lead to sebaceous glands hypertrophy with increased sebum secretion, increased production of skin surface lipids and increased proliferation of P. acnes [7,8]; (viii) using improper cosmetics -i.e. comedogenic (blocking pilosebaceous units) or aggressive alcoholic cosmetic preparations (which initially cause skin dryness, and thus predispose to sebum overproduction) [9].…”
Section: Introductionmentioning
confidence: 99%